Validação de perfil de competências na formação : perspectiva de enfermeiros da área profissional - Cioffi, Andréia Correia de Souza (2017)
ABSTRACT: This research had the overall objective of validating the content of a profile of competences for the training of the nursing professional in the fields of health care, administration and management, education, knowledge production and their evaluation criteria, which are performances to be observed in the trainee. The specific objectives included reformulating the profile based on contributions from the nursing appraisers (expert judges and peers) and analyzing how these actors understand the fields of competence permeating the performance of this professional. This is a convergent study with mixed methods and a quantitativequalitative approach, which was conducted in three hospitals in Cuiabá-MT, using the conceptual framework of professional competence. We set forth a level of agreement equal to or greater than 70% for the content validation, and the data collection took place by means of the Delphi technique and a virtual questionnaire containing the profile of competences, in the SurveyMonkey program, sent by e-mail to the participants. It was developed in two steps: the first was the validation by expert judges, totaling 28, and the second by peers, totaling 72. In both cases, we reached a consensus greater than 70%, in a single Delphi round. In order to analyze the data, we used the mixed methods analysis adapted from Creswell and Clark. The quantitative analysis was performed through simple descriptive statistics; and, in order to evaluate the concordance, we calculated the Content Validity Index (CVI) and the binomial test. The qualitative analysis was performed on the basis of literature, conceptual framework of professional competence and content analysis of the thematic type. Regarding the results of the first step, the competence related to health care and evaluation criteria was approved with 93%; the competence related to administration and management and evaluation criteria with 95%; the competence related to education and evaluation criteria with 95%; and the competence related to knowledge production was validated with 92%. Based on the contributions from the expert judges, the profile underwent changes, which led us to obtain the second version of the matrix of competences, which again was submitted to content validation, this time with the peers, where the competence related to health care and evaluation criteria was approved with 97%; the competence related to administration and management and evaluation criteria with 95%; the competence related to education and evaluation criteria with 98%; and the competence related to knowledge production and evaluation criteria with 91%. Accordingly, we proceeded to the new reformulation of the profile of competences from the contributions from the peers, resulting in the third and ultimate version. We have concluded that the validated profile of competences can be used in different contexts of the country and implemented in the PPC (educational project) of the Undergraduate Nursing Course at FAEN/UFMT. Nurses envisage the importance of mobilizing the four fields of competences in practice, but they highlight several difficulties to implement them in the work environment. We can realize the need for discussions and a solid articulation of the issue of professional competences between the training and the professional exercise of the nurse.